MENINGKATKAN AKTIVITAS, BERPIKIR KRITIS DAN HASIL BELAJAR PADA MUATAN PPKN MENGGUNAKAN MODEL PINTU PADA KELAS V SDN MANARAP LAMA 1 - Fatimatuzzahra; Ari Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problems in this research include the lack of activity, critical thinking, and student learning outcomes. This is because teacher-centered learning is still used and students find it difficult to understand the content of socio-cultural diversity of Indonesian society in PPKn material. To solve this problem, efforts were made through the application of the PINTU learning model which combines the Problem Based Learning, Think Pair Share, and Course Review Horay models. This study aims to improve activity, critical thinking, and student learning outcomes which are carried out using Classroom Action Research (CAR), qualitative and quantitative. The results of the study prove that teacher activity in P1 scored 22, so that it increased significantly from each meeting to get 31 which is categorized as "Very Good" in P4. Then, P1 in student activity 1 reached 8% for the "Less Active" criteria, but this result increased from each meeting until it was categorized as "Very Active" with a percentage of 77% in P4. Meanwhile, P1 in critical thinking skills reached 4% in the "Less Skilled" criteria, but this value increased until P4 so that it was categorized as "Very Skilled" with a percentage of 77%. Then, P1 on classical completeness of student learning outcomes was 31% and 100% on P4 which was categorized as "Complete". The results of the study concluded that the application of the PINTU model can increase teacher activities, student activities, critical thinking skills, and student learning outcomes.